PENGARUH PEMBERIAN LARUTAN GULA KELAPA DAN JUS UMBI BIT TERHADAP BOBOT ORGAN USUS HALUS, PROVENTRIKULUS DAN VENTRIKULUS PADA ANAK AYAM BROILER - Zitni Ilma; Retno Murwani; Rina Muryani (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2016)
The aim of this study was to determine the effect of palm sugar and beet juice in drinking water on relative weight of small intestine, proventriculus, and ventriculus of broiler chickens. One hundred and ninety five unsexed day old chicks (DOC) strain cobb were completely randomized into 5 treatments: T0 (control), T1 (1% palm sugar solution), T2 (1% beet root juice), T3 (2% palm sugar solution), and T4 (2% beet root juice). Palm sugar solution and beet root juice were given as drinking water. Chick from each treatment was taken on 2th, 3th, and 4th day. The chicks were sacrificed then dissected, small intestine, proventriculus, and ventriculus were taken and weighed. The results showed that 1 % and 2% palm sugar and beet juice in dringking water increased relative weight of small intestine at 4th day.